2014
DOI: 10.1038/clpt.2013.255
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Iontophoresis of Treprostinil in Systemic Sclerosis: A Proof-of-Concept Study

Abstract: Ischemic digital ulcer (DU) is a serious complication of systemic sclerosis (SSc). Intravenous prostanoids are the only approved treatment for active DUs, but they induce dose-limiting side effects and require hospitalization. Our objective was to evaluate the effect of iontophoresis (a noninvasive drug delivery method) of treprostinil in SSc patients. Three studies were conducted: a pharmacokinetic study in 12 healthy volunteers showed that peak dermal concentration was reached at 2 hours, whereas plasma trep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…Such data are consistent with our previous report on healthy volunteers forearm (Blaise et al, 2013), while on the finger pads of systemic sclerosis patients, the duration of the hyperemia was shorter (Roustit et al, 2014b). Other groups have tested the effects of prostacyclin analogs on skin microcirculation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Such data are consistent with our previous report on healthy volunteers forearm (Blaise et al, 2013), while on the finger pads of systemic sclerosis patients, the duration of the hyperemia was shorter (Roustit et al, 2014b). Other groups have tested the effects of prostacyclin analogs on skin microcirculation.…”
Section: Discussionsupporting
confidence: 92%
“…This explains why plasma monitoring showed negligible systemic diffusion of the drug. We used a liquid chromatography -tandem mass spectrometry method that has a very low detection threshold (Roustit et al, 2014b). Indeed, the highest plasma concentration detected, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More important, PGI 2 analogs are potent medications to treat IPAH. Treprostinil is a PGI 2 analog that increases cutaneous blood flow when administered by cathodal iontophoresis to healthy volunteers (10) and patients with systemic sclerosis (11). We hypothesize that patients with IPAH have systemic abnormalities in the PGI 2 pathway that can be tested in vivo by cutaneous treprostinil iontophoresis.…”
Section: To the Editormentioning
confidence: 99%
“…Effective topical therapies which act locally on the digits, and which are free from systemic side effects, are badly needed. It is encouraging that both preclinical and human studies are exploring topical delivery systems, including with iontophoresis, to improve blood flow [66,67,68]. An exciting potential development is the prospect of being able to apply local therapies to ulcers to induce angiogenesis and promote healing: a study in UCD-206 chickens showed that application of VEGF 121 -fibrin in a gel matrix improved This prospective study of 623 patients (59 centres from 14 countries) reported that among the 468 patients with a previous history of digital ulceration, the three strongest predictors of new ulcers over 6 months were (at baseline) the mean number of capillaries/mm in the middle finger of the dominant hand, the number of digital ulcers, and the presence of critical ischaemia.…”
Section: Topical Therapiesmentioning
confidence: 99%